The Importance of Remote Sensing Technology and its use in the Study of Environmental Systems (Detection of Groundwater, Model) - Assistant Prof. Dr. / Abd AL- Salam Muhammad Mail Aljughaifi. (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The main objective of this research know is to evaluate the ability remote sensing techniques to detect ground water in the study area.To achieve this goal, American satellite imagery (Landsat-7) was used to cover the study area. And use of the digital image processor program (ERDAS IMAGINE)(Earth Resources Data Analysis System)in order to improve aerial image and the signature of the real coordinates of the area and classified according to the nature of the region, then analyze this image by comparing them with geophysical methods used to identify groundwater wells. This analysis of the ability of remote sensing techniques and digital image processing has proven to identify groundwater sites depending on the study and classification of the surface crust covering the area, which provides an effective tool for exploring groundwater.